2016
DOI: 10.14720/aas.2016.107.2.14
|View full text |Cite
|
Sign up to set email alerts
|

Bioefficacy of some biorational insecticides for the control of Aphis gossypii Glover, 1877, (Hemiptera: Aphididae) on greenhouse grown cucumber

Abstract: <p><em></em><em></em><em>Aphis gossypii</em> Glover, 1877 is a serious pest of cucumber in greenhouse plantings. Biorational insecticides are an alternative of broad spectrum insecticides for aphid suppression in greenhouse. In this regards, the efficiency of some biorational insecticides including soap based on coconut oil, surfactant based on sodium sulfosuccinate and antifeeding based on potassium nicotinate were assayed on <em>A</em>. <em>gossypii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The current results recommend that three consecutive spraying are necessary to achieve the best control. These findings highly corroborates the investigation of Emami [19] where he used four organically-farming insecticides, among which was the nimbecidine extract, and assured that applying the products for 3 times gave excellent control. Therefore, repeating applications may be necessary for better pest control [20].…”
Section: Discussionsupporting
confidence: 83%
“…The current results recommend that three consecutive spraying are necessary to achieve the best control. These findings highly corroborates the investigation of Emami [19] where he used four organically-farming insecticides, among which was the nimbecidine extract, and assured that applying the products for 3 times gave excellent control. Therefore, repeating applications may be necessary for better pest control [20].…”
Section: Discussionsupporting
confidence: 83%
“…Palizin performs better than mospilan in reducing eggs and nymphs pistachio psylla, A. pistaciae (Danaye-Tous and Farazmand 2014). Moreover, Emami (2016) showed that the best mortality rate in biorational pesticide treatments was obtained in three days, with a 78.5% mortality rate on the Aphis gossypi population. Previous research indicates that the effects of botanical pesticides like Palizin on the citrus black aphid, Toxoptera aurantii Boyer consist of79.75, 95.59, and 96.39% pest mortality rates at 24, 48, and 72 hours after treatment, respectively (Gholamzadeh-Chitgar and Pourmoradi 2017).…”
Section: Discussionmentioning
confidence: 98%